In vivo monitoring of leukemia-niche interactions in a zebrafish xenograft model. - Anja Arner; Andreas Ettinger; Bradley Wayne Blaser; Bettina Schmid; Irmela Jeremias; Nadia Rostam; Vera Binder-Blaser (PLoS ONE)
Acute lymphoblastic leukemia (ALL) is the most common type of malignancy in children. ALL prognosis after initial diagnosis is generally good; however, patients suffering from relapse have a poor outcome. The tumor microenvironment is recognized as an important contributor to relapse, yet the cell-cell interactions involved are complex and difficult to study in traditional experimental models. In the present study, we established an innovative larval zebrafish xenotransplantation model, that allows the analysis of leukemic cells (LCs) within an orthotopic niche using time-lapse microscopic and flow cytometric approaches. LCs homed, engrafted and proliferated within the hematopoietic niche at the time of transplant, the caudal hematopoietic tissue (CHT). A specific dissemination pattern of LCs within the CHT was recorded, as they extravasated over time and formed clusters close to the dorsal aorta. Interactions of LCs with macrophages and endothelial cells could be quantitatively characterized. This zebrafish model will allow the quantitative analysis of LCs in a functional and complex microenvironment, to study mechanisms of niche mediated leukemogenesis, leukemia maintenance and relapse development.